Smooth-muscle myosin mutations in hereditary non-polyposis colorectal cancer syndrome. - Vickaryous, N; Polanco-Echeverry, G; Morrow, S; Suraweera, N; Thomas, H; Tomlinson, I; Silver, A (2008)
We examined adenomas and cancers from hereditary non-polyposis colorectal cancer (HNPCC) syndrome patients for the presence of frameshift mutations in the smooth-muscle myosin gene, MYH11. Our results show that mutations in MYH11 occur more frequently in cancers than adenomas (P=0.008) and are dependent on microsatellite instability (MSI+).